PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN PENGGUNA TOKOPEDIA DI BANDAR LAMPUNG - Rianadia Agustina; Driya Wiryawan; Nuzul Inas Nabila (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Covid-19 pandemic in 2020 limited people's mobility so that they could not make purchases directly to the market. Various advantages of e-commerce make online shopping the main choice of the public in meeting their needs, one of which is Tokopedia. Tokopedia was hit by an issue related to a case of hacking user data in 2020 as reported by CNBC Indonesia.com. Tokopedia is faced with choices when shopping offline and online, including consumers can assess directly and see product rating reviews from other consumers. Based on reviews, there are still low ratings by consumers. This study aims to determine the effect of service quality and trust on consumer satisfaction of Tokopedia users. The population of this study was Tokopedia users living in Bandar Lampung, with a total sample of 110 respondents. The sample used in this study was non-probability sampling with purposive sampling technique. The analysis used in this study is a validity test, reliability test, multiple linear regression analysis, and hypothesis testing, namely the t test and coefficient of determination (R2) with the help of the SPSS 26 application program. The results of this study show that the variables of service quality and trust have a significant influence on consumer satisfaction.